Preflight Weather Decision Support Tool (PWDST): User-Centered Design Process and Usability Validation. (November 2019) - King, Jayde; Kleber, John; Harris, Ashlee; Chaparro, Barbara; Blickensderfer, Beth
General Aviation flight operations have been negatively affected by the slow decreasing weather related accident rate for the last 20 years. Upon further investigation, research suggests, that poor preflight planning and a lack of aviation weather experience and knowledge may be contributing factors to the stagnant weather related accident rate. Our team developed a Preflight Weather Decision Support Tool (PWDST) to help novice pilots access, interpret, and apply weather information. We used a user-centered design process which involved an initial task analysis, low-fidelity prototyping, low-fidelity usability testing, user interviews and expert review. This study assessed and compared the perceived usability, difficulty, and the system assistance satisfaction of the PWDST. Participants (n=9) completed a usability study and a series of surveys during, as well as, after the completion of the preflight planning scenario. A series of Mann-Whitney U Tests were conducted to compare the difference between Private Pilot and Certified Flight Instructors (CFI) perceived usability, difficulty, and system assistance satisfaction ratings. Results indicated, there were no significant differences between group ratings. Overall, both groups reported above average usability, system assistance and low difficulty rating for the PWDST. Future research and possible implications are discussed.